The Effect of Worn Hinges of the Cultivator Section on the Quality of Row-To-Row Processing of Cotton - Abdimominov, Ikromjon Iminovich (American Journal of Biodiversity, 2025)
The installation of the cultivator’s working bodies at a relatively large distance from the row axis is due to a number of reasons: poor handling of the tractor in rows, the placement of working bodies relative to the wheel, large transverse fluctuations due to increased gaps in the hinges of the cultivator section, the type of working bodies, speed of movement, etc. in practice, protective zones are determined mainly by the greatest deviation of plant shoots and working bodies.